2007
DOI: 10.1213/01.ane.0000260616.49050.6d
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis and Surgery: Past, Present, and Future

Abstract: Hypnosis has been defined as the induction of a subjective state in which alterations of perception or memory can be elicited by suggestion. Ever since the first public demonstrations of "animal magnetism" by Mesmer in the 18th century, the use of this psychological tool has fascinated the medical community and public alike. The application of hypnosis to alter pain perception and memory dates back centuries. Yet little progress has been made to fully comprehend or appreciate its potential compared to the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 78 publications
2
45
0
2
Order By: Relevance
“…In our study, only 2 patients required pharmacological therapy for PONV. Previous studies have shown that hypnosis is effective for prevention of nausea and vomiting [1,2,18,19]. All 15 patients in our study also had smooth postoperative course and reported complete amnesia for intra-operative events.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In our study, only 2 patients required pharmacological therapy for PONV. Previous studies have shown that hypnosis is effective for prevention of nausea and vomiting [1,2,18,19]. All 15 patients in our study also had smooth postoperative course and reported complete amnesia for intra-operative events.…”
Section: Discussionsupporting
confidence: 64%
“…Although hypnotism is known to have been practiced by many people, it was James Braid who popularised its use in anesthesia. With the advent and rapid popularity of nitrous oxide, ether and chloroform, and also thanks to the discredit from the use of hypnosis by stage hypnotists and charlatans, the use of hypnosis in anesthesia dwindled [2]. The regained interest and use of hypnosis in anesthesia practice can be largely attributed to the recognition by British Medical Association (1995) and American Medical Association (1958).…”
Section: Introductionmentioning
confidence: 99%
“…Although suggestions are one of the most important tools of hypnosis, suggestive techniques can be successfully used without formal hypnosis induction as well [20]. Studies support that suggestions have beneficial impact on various surgical outcomes [22,23], and specifically on mitigating procedural anxiety (e.g. [24][25][26]).…”
Section: Introductionmentioning
confidence: 99%
“…> Im Trancezustand kann ein posthypnotischer Auftrag gegeben werden [19]. Wie effektiv solche positiven Suggestio nen wirken, zeigt auch die Anwendung von Hypnose in der Zahnmedizin [50] und Medizin [52], speziell bei operativen Eingriffen [2,28,44,67], belastenden Un tersuchungen wie Endoskopien [3,30], bei Venenpunktion [38] und in der Schmerz therapie [44,46]. So wurde z.…”
Section: Positivsuggestionen Verwendenunclassified
“…Zahlreiche Studien haben güns tige Effekte bei Patienten unter Allgemein anästhesie nachgewiesen, denen intra operativ Suggestionen direkt oder über Band zugesprochen wurden. Es wurden eine verringerte Inzidenz von PONV, Fie ber und Kopfschmerz, eine größere hä modynamische Stabilität, ein geringe rer postoperativer Analgetikabedarf, eine frühere Mobilisation und eine verkürz te Krankenhausliegedauer nachgewiesen [13,18,44,45,67]. Aus diesen klinischen Untersuchungen und der Hypnosefor schung sind vielfältige Wirkungen von positiven Suggestionen auf unterschied liche Parameter und Symptome bekannt (.…”
Section: Positivsuggestionen Verwendenunclassified